Control de inventario de la casa suspensión el amortiguador del Cantón Ambato, provincia de Tungurahua, periodo 2022 - Jordan Peña, Timoteo Omar (2023)
The case study called "Inventory control of the Suspension House El Amortiguador of the Ambato canton, Tungurahua province, period 2022" which has the objective of evaluating the inventory control carried out in the Suspension House El Amortiguador of the Ambato canton during the period 2022 through contrasting the bibliographic findings and the processes that are carried out on a recurring basis, the same that are carried out based on the line of research "Financial, administrative, tax, audit, control management" and the subline "audit and control" that corresponds to the Accounting and auditing career, on the other hand, the methodology that refers to the descriptive and analytical method is taken into account. While the techniques used to collect sufficient information are the observation carried out through a visit to the warehouse area, the interview carried out with the owner of the company and documentary research, all of which are carried out through the respective documents, which give as a result that the inventory control processes are carried out by means of a matrix prepared in the Excel office tool, where the existing products are detailed, but not their units, as consequences it affects when it comes to knowing the Inventory turnover and the replacement period, therefore, do not present the necessary units to cover the demand for products, in addition to this, it violates the accounting processes that have an impact when making decisions.